Shocks, social protection, and resilience: Evidence from Ethiopia - Knippenberg, Erwin; Hoddinott, John F. (International Food Policy Research Institute, 2017)
The malign effect of shocks has long been a concern within economics, partly because they result in transitory welfare losses and partly because they may have persistent effects. In development discourse, this latter concern has spurred interest in the concept of resilience and how public interventions can enhance resilience. Within this context, we assess the impact of a social protection program, Ethiopia’s Productive Safety Net Program, on the longer term impacts of drought on household food security. We find that drought shocks reduce the number of months a household considers itself food secure and that these impacts persist for up to four years after the drought has ended. Using a Hausman instrumental variable estimator, we find that receipt of PSNP payments reduced the initial impact of drought shocks by 57 percent and eliminates their adverse impact on food security within two years. In this way, the PSNP strengthens the resilience of its beneficiaries against adverse shocks. This impact is largest for PSNP beneficiaries with little or no land. Results are robust to using an objective measure of drought derived from satellite data, the Standard Evapotranspiration Index. They are also robust to changes in sample composition, the presence of other interventions, and the estimator used.